Mennonite women's societies in Canada: A historical case study. - Redekop, Gloria L. Neufeld. (University of Ottawa (Canada), 1993)
This study is a social history of Canadian Mennonite women's societies in the two largest Russian Mennonite denominations in Canada--the Conference of Mennonites in Canada (CMC) and the Mennonite Brethren (MB). Using archival materials and information generated by the author's survey, the thesis traces the growth and decline of Mennonite women's societies in Canada within CMC and MB churches established during the three periods of Russian immigration to Canada. Set within the historical context of the role of Mennonite women from the time of Anabaptism in the Netherlands, and through subsequent migrations to Prussia and Russia, it explores the development of Mennonite women's societies in Canada in the light of the changing role of Mennonite women both in the church and in society. It suggests that, in the early years, Mennonite women's societies gave Mennonite women an opportunity to serve God and fully participate in worship at a time when their roles were restricted in the church. In later years, interest in Mennonite women's societies declined. This thesis argues that Mennonite women's societies became a context for women's service to God. Motivated by the call of God through the biblical text, it was here that they organized for the support of missions as they raised money in their own creative ways. It was a context as well for fellowship and mutual support as women. For Mennonite women, their societies were also an avenue for spiritual growth. In their regular meetings they developed a worship ritual that was so strikingly similar to the components of the Sunday morning worship service in the church that we could say Mennonite women's societies functioned as a parallel church for Mennonite women. The decline of Mennonite women's societies occurred along with other trends in the church and society. Women were gradually being included within the official church structure. First they were granted the vote at church business meetings. Then their role was enlarged and they were able to take positions on church boards and committees. Not only were women becoming more involved in the church, they were also becoming more integrated into Canadian society. The women's movement did not leave Mennonite women untouched. From the late 1960s, they began to pursue higher education and employment outside the home. Concurrent with the changes in women's roles in church and society came a self-questioning of the usefulness of Mennonite women's societies as interest in membership was declining.
Keywords: Religion, History of.